Textile waste management and recycling opportunities and challenges for Africa: a mini-review - Peter Davis Sumo (The Holistic Approach to Environment, 2024)
Global fibre supply increased to 113 million tonnes in 2021, contributing to elevated energy and water consumption levels, agricultural pollution, and post-consumer textile waste. Introducing second-hand clothing as an alternative to mitigate textile waste is advantageous for providing affordable clothing. However, the disposal of substandard and unsold garments obstructs riverways and drainage systems, leading to flooding. Moreover, incineration produces heightened greenhouse gas emissions, exacerbating poverty and impeding development, particularly in Africa. Nevertheless, textile wastes present opportunities for establishing large-scale regeneration and recycling facilities, offering the potential for employment generation and skill development in Africa. This mini-review aims to underscore Africa’s potential and challenges in textile waste recycling. The findings underscore the importance of recognizing African textile waste, both as an environmental hazard and as a valuable resource for the production of new clothing. Additionally, they emphasize how efforts to add value to recovered textiles are gaining traction, particularly in East, South, and North Africa. However, no formal textile recycling facilities were identified in West and Central Africa. This mini-review is constrained by data limitations, encouraging future researchers to broaden its scope by examining individual countries and recycling companies.